2017
DOI: 10.1039/c6rp00202a
|View full text |Cite
|
Sign up to set email alerts
|

An examination of student outcomes in studio chemistry

Abstract: Twenty years ago, a major curriculum revision at a large, comprehensive university in the Western United States led to the implementation of an integrated lecture/laboratory (studio) experience for our engineering students taking general chemistry. Based on these twenty years of experience, construction of four purpose-built studio classrooms to house the majority of the remaining general chemistry courses was completed in 2013. A detailed study of the effects of the entire ecology of the studio experience on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 68 publications
(91 reference statements)
0
14
0
Order By: Relevance
“…Curriculum design at our own university has led to the development of studio classrooms for general chemistry courses, which integrate the laboratory and lecture portions of the course into one space and time period. The studio classroom helps students to explicitly connect concepts taught in lecture through experimentation, resulting in improved exam scores, more expert-like learning attitudes, and positive assessments of the active learning environment from both students and instructors ( Kiste et al, 2017 ). In order to apply these findings and address the lack of active learning opportunities for transcription and translation in our biochemistry curriculum, we sought to incorporate cell-free protein synthesis (CFPS) into our classroom laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Curriculum design at our own university has led to the development of studio classrooms for general chemistry courses, which integrate the laboratory and lecture portions of the course into one space and time period. The studio classroom helps students to explicitly connect concepts taught in lecture through experimentation, resulting in improved exam scores, more expert-like learning attitudes, and positive assessments of the active learning environment from both students and instructors ( Kiste et al, 2017 ). In order to apply these findings and address the lack of active learning opportunities for transcription and translation in our biochemistry curriculum, we sought to incorporate cell-free protein synthesis (CFPS) into our classroom laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…At a different institution, 227 students in an LA-supported chemistry course were surveyed and respondents agree that the course is better suited for learning (≈90%) and they are more motivated (≈65%) and enjoy the course (≈80%) more than in courses without LAs. Additionally, students agree that in LA-supported courses, they interact more with their peers (≈90%) and concepts are better connected (≈75%), which could explain why LAs increase enjoyment, understanding, and appreciation for course material (Kiste, Scott, Bukenberger, Markmann, & Moore, 2017).…”
Section: Talbot (2013)mentioning
confidence: 99%
“…Variations on this style of course delivery have been implemented at a variety of institutions and in a variety of subject areas during the last few decades, including in Cal Poly chemistry and physics courses (Bailey, Kingsbury, Kulinowski, Paradis, & Schoonover, 2000; Kiste, Scott, Bukenberger, Markmann, & Moore, 2017). Early work, which established a framework for studio delivery, anecdotally reported very positive feedback from students and instructors, resulting in more widespread adoption and more rigorous evaluation of the approach (Altmiller, 1973; Apple & Cutler, 1999; Laws, 1991, 1997; Wilson & Jennings, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Beichner and Saul (2003) found that students in studio sections had better scores on 8 out of 9 standardized exam questions, Roy (2003) measured a roughly 50% greater improvement in performance on post‐ vs. pre‐tests with a studio approach, Cummings (2008) documented improvements in normailzed gain for multiple subject areas, and Kiste et al. (2017) found significant improvements in learning and increased engagement in studio sections. Positive attitude or behavior outcomes (without considering learning) were documented by Wilson (1994), who found end‐of‐semester surveys showed nearly twice as many students in studio‐style sections agreed that they enjoyed the course relative to those in a traditional section, and Lux (2002), who saw retention rates at a community college increase from around 50% in traditional sections to 80% in a studio section.…”
Section: Introductionmentioning
confidence: 99%